Receptive vocabulary assessment in preschoolers using an automated auditory word recognition task (REVOC: 1) - Norambuena Albornoz, Yeniè; Sáez Carrillo, Katia; Riffo Ocares, Bernardo; Gutiérrez Gómez, Fernando (Boletín de Filología, 2023)
The paper presents the first results obtained with REVOC: 1, an automated auditory word recognition task used to assess receptive vocabulary in Spanish-speaking preschoolers. The task was programmed in Unity for 8´ tablets in a self-application mode and included accuracy and response time as parameters. Non-probabilistic sampling was used. The sample consisted of 242 monolingual Chilean children between 4 and 6 years old. The list of vocabulary stimuli was extracted from TEVI-R, a paper-based test that assesses receptive (hearing) vocabulary. To estimate the automation’s functionality and the parameters’ values, the performance by age group at both global and item levels was evaluated. The results demonstrated a high level of performance in the selected items, with significant differences by age group in both accuracy and response time. The accuracy correlated negatively with total and correct latencies, with significant differences between age groups. The contrast by items allowed us to appreciate the time-precision relationship modulated by age, and the effect of word difficulty on latency. REVOC:1 adequately assessed receptive vocabulary and can advance to new stages of development.